2017
DOI: 10.3906/sag-1701-77
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the general characteristics of patients aged 85 years and above admitted to a university hospital emergency department

Abstract: Background/aim: The number of elderly people (≥65 years old) is increasing both in Turkey and internationally due to improved living conditions and decreased mortality rates. Knowing the characteristics of elderly patients admitted to emergency departments can provide guidance for diagnosis and treatment approaches. In this study, we analyzed the characteristics of very old patients (≥85 years old) admitted to the emergency department and put together data for use in forward planning in healthcare services. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…Considering the distribution of case admissions by months in our study, it was observed that the most frequent months were December, November and October, respectively. Although there are differences in the literature regarding of the frequent admission months, however it was observed that the geriatric patient group admitted most frequently in autumn and winter season [10,11]. This might be explained by the seasonal flu period starting from mid-autumn to early spring and the resistance of geriatric patients to respiratory infections is different from other age groups.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Considering the distribution of case admissions by months in our study, it was observed that the most frequent months were December, November and October, respectively. Although there are differences in the literature regarding of the frequent admission months, however it was observed that the geriatric patient group admitted most frequently in autumn and winter season [10,11]. This might be explained by the seasonal flu period starting from mid-autumn to early spring and the resistance of geriatric patients to respiratory infections is different from other age groups.…”
Section: Discussionmentioning
confidence: 89%
“…The discharge rate of patients who were admitted only once was 84.2% and the rate was 88.4% for twice and more admissions. In the study of Demircan et al, they mentioned that the re-application rate was 37% in one-year period [11], in another study, this rate was reported as 50% [6]. Patients whose acute treatment is completed in the emergency department and have no indication for hospitalization should be followed by appropriate polyclinics or home care services.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease and other forms of dementia disproportionally affect people with lower educational attainment who are less likely to be eligible for pensions associated with formal employment [26]. There is also evidence of trends towards extended hospitalisations [27], use of emergency services [28] and the admission of frail, older people to health facilities due to lack of LTC services in the community [29].…”
Section: Population Ageing In Turkeymentioning
confidence: 99%
“…In Turkey, according to data of the Turkey Statistics Institute reported in 2016, the number of elderly has increased by 17.1% in the last 5 years, and the proportion of the elderly has reached to 8.3% of the population by the end of 2016 (2). Consistent with this increase in the elderly population, the rate of admission of elderly patients to hospitals, particularly to emergency departments (EDs) and intensive care units (ICUs), is also gradually increasing (3)(4)(5)(6)(7). Admission rates of elderly patients are variable in different countries, cities and regions (4).…”
Section: Introductionmentioning
confidence: 95%
“…Consistent with this increase in the elderly population, the rate of admission of elderly patients to hospitals, particularly to emergency departments (EDs) and intensive care units (ICUs), is also gradually increasing (3)(4)(5)(6)(7). Admission rates of elderly patients are variable in different countries, cities and regions (4). In addition, the admission rates of elderly patients to EDs vary according to the population and socioeconomic status of the elderly in the city; location and total number of hospitals in the city and characteristics of the hospital, such as bed capacity (5,8).…”
Section: Introductionmentioning
confidence: 99%